2020
DOI: 10.1038/s41586-019-1898-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-targeted maternal antibodies protect neonates from enteric infection

Abstract: Although maternal antibodies protect newborn babies from infection 1,2 , little is known about how protective antibodies are induced without prior pathogen exposure. Here we show that neonatal mice that lack the capacity to produce IgG are protected from infection with the enteric pathogen enterotoxigenic Escherichia coli by maternal natural IgG antibodies against enterotoxigenic E. coli when antibodies are delivered either across the placenta or through breast milk. By challenging pups that were fostered by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 44 publications
(44 reference statements)
3
116
0
Order By: Relevance
“…This suggests that donor milk may be inferior to maternal milk in an immunological capacity only, retaining qualities sufficient to influence C. perfringens colonisation patterns in some contexts. It has recently been demonstrated that neonatal mice can be protected from enteric infection by antibodies delivered through breast milk [39]. The absence of competing milk commensals in donor milk may perhaps further explain why in our study it failed to influence C. perfringens carriage in the way that maternal milk did.…”
Section: Discussionmentioning
confidence: 55%
“…This suggests that donor milk may be inferior to maternal milk in an immunological capacity only, retaining qualities sufficient to influence C. perfringens colonisation patterns in some contexts. It has recently been demonstrated that neonatal mice can be protected from enteric infection by antibodies delivered through breast milk [39]. The absence of competing milk commensals in donor milk may perhaps further explain why in our study it failed to influence C. perfringens carriage in the way that maternal milk did.…”
Section: Discussionmentioning
confidence: 55%
“…Infections are also prevented indirectly by NAb binding self-receptors such as CCR5, essential for the entry of the HIV virions (158). Maternal natural IgG antibodies protected neonatal mice from infection with enterotoxigenic E. coli infections when these antibodies were delivered across the placenta or through milk (159).…”
Section: Natural Antibodies Against Pathogens and Infectionsmentioning
confidence: 99%
“…This suggests that donor milk may be inferior to maternal milk in an immunological capacity only, retaining qualities sufficient to influence C. perfringens colonisation patterns in some contexts. It has recently been demonstrated that neonatal mice can be protected from enteric infection by antibodies delivered through breast milk (39). The absence of competing milk commensals in donor milk may perhaps further explain why in our study it failed to influence C.…”
Section: Discussionmentioning
confidence: 60%